Optimalisasi Pembelajaran Praktik Keterampilan Mengajar (PKM) Dalam Pelaksanakaan Program Asistensi Mengajar (AM) - Lathifah, Faiqotul; Mahbubah, Sahiyatul; Angraini, Melsi; Bashith, Abdul (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3143, 2024)
The success of the Teaching Assistance program is supported by the optimal implementation of Teaching Skills Practice (PKM) learning. The good or bad implementation of PKM learning has close implications for the achievement of Learning (CPL) and the success of the Teaching Assistance (AM) program. The purpose of this study was to determine the implementation of Teaching Skills Practice (PKM) learning and the implementation of the Teaching Assistance program in the Social Sciences Education Department, FITK UIN Maulana Malik Ibrahim Malang. The research method uses a qualitative approach with a descriptive analysis research type. The results of the study explain that: The implementation of the Teaching Assistance student program in the Social Sciences Education Department is not optimal and there are still many things that need to be evaluated again, because students are not ready to be deployed to the field. Efforts that can be made to optimize PKM learning in the Social Sciences Education Department are providing learning evaluation courses before implementing teaching assistance, socializing the process of compiling independent curriculum learning devices, providing training on learning media innovation, workshops on developing learning models and strategies, and in the implementation of teaching skills practice courses, it is necessary to emphasize an explanation of the importance of teacher professional ethics.